Distinct structural changes in wild-type and amyloidogenic chicken cystatin caused by disruption of C95–C115 disulfide bond. Issue 12 (1st December 2016) - Chong, Xiaoying; Lu, Xian; Wang, Yu; Chang, Alan K.; Xu, Linan; Wang, Na; Sun, Yonghui; Jones, Gary W.; Song, Youtao; Song, Yong-Bo; He, Jianwei
Abstract : Human cystatin C (HCC) amyloid angiopathy (HCCAA) is characterized by tissue deposition of amyloid fibrils in blood vessels, which can lead to recurrent hemorrhagic stroke. Wild-type HCC forms part of the amyloid deposits in brain arteries of elderly people with amyloid angiopathy. A point mutation causing a glutamine to a leucine substitution at residue 68 in the HCC polypeptide chain greatly increases the amyloidogenic propensity of HCC and causes a more severe cerebral hemorrhage and premature death in young adults. In this study, we used molecular dynamics simulations to assess the importance of disulfide bridge formation upon the stability of chicken cystatin and how this may influence the propensity for amyloid formation. We found that disulfide bridge formation between Cys95 and Cys115 in human cystatin played a critical role in overall protein stability. Importantly, Cys95–Cys115 influenced cystatin structure in regions of the protein that play key roles in the protein-folding transitions that occur, which enable amyloid fibril formation. We hypothesized that correct disulfide bridge formation is a critical step in stabilizing cystatin toward its native conformation. Disrupting Cys95–Cys115 disulfide bridge formation within cystatin appears to significantly enhance the amyloidogenic properties of this protein. In addition, by combining in silico studies with our previous experimental results on Eps1, a molecular chaperone of the PDI family, we proposed that age-related HCCAA, may possess a different pathogenic mechanism compared with its amyloidogenic counterpart, the early onset amyloidogenic cystatin-related CAA.